2012
DOI: 10.1038/ng.2411
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association analyses of esophageal squamous cell carcinoma in Chinese identify multiple susceptibility loci and gene-environment interactions

Abstract: We conducted a genome-wide association study of gastric cancer (GC) and esophageal squamous cell carcinoma (ESCC) in ethnic Chinese subjects in which we genotyped 551,152 single nucleotide polymorphisms (SNPs). We report a combined analysis of 2,240 GC cases, 2,115 ESCC cases, and 3,302 controls drawn from five studies. In logistic regression models adjusted for age, sex, and study, multiple variants at 10q23 had genome-wide significance for GC and ESCC independently. A notable signal was rs2274223, a nonsynon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
203
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 244 publications
(217 citation statements)
references
References 42 publications
12
203
0
2
Order By: Relevance
“…They confirmed the known association of the ALDH2 locus on 12q24 to ESCC, and a joint analysis showed that drinkers with both of the ADH1B and ALDH2 risk alleles had a fourfold increased risk for ESCC compared to drinkers without these risk alleles. Their results underscore the direct genetic contribution to ESCC risk, as well as the genetic contribution to ESCC through interaction with alcohol consumption [55] . There are also some studies on polymorphism on other locations for esophageal adenocarcinoma with smaller samples.…”
Section: Zhang Y Risk Factors Of Esophageal Cancermentioning
confidence: 86%
See 1 more Smart Citation
“…They confirmed the known association of the ALDH2 locus on 12q24 to ESCC, and a joint analysis showed that drinkers with both of the ADH1B and ALDH2 risk alleles had a fourfold increased risk for ESCC compared to drinkers without these risk alleles. Their results underscore the direct genetic contribution to ESCC risk, as well as the genetic contribution to ESCC through interaction with alcohol consumption [55] . There are also some studies on polymorphism on other locations for esophageal adenocarcinoma with smaller samples.…”
Section: Zhang Y Risk Factors Of Esophageal Cancermentioning
confidence: 86%
“…The genome-wide association studies (GWAS) has emerged as a powerful and successful tool to identify common disease alleles by using high-throughput genotyping technology to interrogate a large number of tagging single nucleotide polymorphisms (SNPs) that serve as surrogates for untested common SNPs across the genome. So far, GWAS of esophageal cancers including ESCC in individuals of European and Japanese ancestry, have shown that variants in ADH genes and/or ALDH2 are associated with risk of ESCC [55][56][57][58] . More recently, Wu et al further reported that nine new ESCC susceptibility loci, of which seven, at chromosomes 4q23, 16q12.1, 17q21, 22q12, 3q27, 17p13 and 18p11, had a significant marginal effect (P = 1.78 × 10 -39 to P = 2.49 × 10 -11 ) and two of which, at 2q22 and 13q33, had a significant association only in the gene-alcohol drinking interaction [gene-environment interaction P (PG × E) = 4.39 × 10 -11 and PG × E = 4.80 × 10 -8…”
Section: The Effects Of Chronic Irritation and Inflammation On Squamomentioning
confidence: 99%
“…Cigarette smoking, heavy alcoholic consumption, micro-nutrient deficiency as well as dietary carcinogen exposure have been identified as main environmental etiological factors of ESCC [1][2][3]. However, only a part of exposed individuals eventually developed ESCC, indicating that host genetic differences may also contribute to ESCC carcinogenesis [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiological evidences indicate that heavy alcohol drinking, tobacco smoking, micronutrient deficiency, and dietary carcinogen exposure are major environmental risk factors of this fatal disease (2,3). However, only a part of exposed individuals eventually develop ESCC, demonstrating that host genetic components may also contribute to ESCC etiology (2)(3)(4)(5)(6)(7).…”
mentioning
confidence: 99%